2021
DOI: 10.3390/pharmaceutics13010100
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Insulin via Skin Route for the Management of Diabetes Mellitus: Approaches for Breaching the Obstacles

Abstract: Insulin is used for the treatment of diabetes mellitus, which is characterized by hyperglycemia. Subcutaneous injections are the standard mode of delivery for insulin therapy; however, this procedure is very often invasive, which hinders patient compliance, particularly for individuals requiring insulin doses four times a day. Furthermore, cases have been reported of sudden hypoglycemia occurrences following multidose insulin injections. Such an invasive and intensive approach motivates the quest for alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 147 publications
(36 reference statements)
0
15
0
Order By: Relevance
“…Porcine ear skin has been often used as a mimicking alternative to the human skin in studies of percutaneous absorption when developing formulations for transdermal delivery of bioactive moieties ( Boscariol et al, 2021 , Silva et al, 2021 , Hernandes et al, 2021 , Jorge et al, 2020 , Campos et al, 2020 , Todo, 2017 , Zakrewsky et al, 2016 ). Several in vitro studies of transdermal permeation using Franz cells have indicated that porcine ear skin is the one that has flow values and permeation coefficients closest to the human skin ( Ahad et al, 2021 , Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Porcine ear skin has been often used as a mimicking alternative to the human skin in studies of percutaneous absorption when developing formulations for transdermal delivery of bioactive moieties ( Boscariol et al, 2021 , Silva et al, 2021 , Hernandes et al, 2021 , Jorge et al, 2020 , Campos et al, 2020 , Todo, 2017 , Zakrewsky et al, 2016 ). Several in vitro studies of transdermal permeation using Franz cells have indicated that porcine ear skin is the one that has flow values and permeation coefficients closest to the human skin ( Ahad et al, 2021 , Islam et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Alternative delivery methods attempted: implantable device, needle-free jet injection, transdermal delivery, microneedle-based delivery, pulmonary delivery [21][22][23][24][25]. There has been a shift in reliance, from synthetic human insulin towards insulin analogues.…”
Section: Type I and Ii Diabetes Mellitusmentioning
confidence: 99%
“…Alternative routes of peptide delivery have been developed and tested. Throughout the years, various new methods have been employed to increase the ease of the delivery of insulin, such as the use of an implantable device [ 21 ], needle-free jet injection [ 22 ], and microneedle-based transdermal delivery [ 23 , 24 ]. Pulmonary delivery of inhalable insulin has been considered as an attractive delivery method, however, it has raised safety concerns with side effects resulting in commercial failures [ 25 ].…”
Section: Synthetic Approach Strategies and Prospects For The Developm...mentioning
confidence: 99%
“…We recommend readers to the two recent reviews describing the different strategies and formulations of transdermal insulin delivery. 62,63 Of these, several versions of jet injectors have completed the final phases in clinical trials, and products including Vitajet 3, InsuJet, Injex, and Comfort-In Needle Free Injectors are available on the market for individuals living with diabetes. Insulin is loaded into a cartridge via adaptors from insulin pens or vials and connected to spring-loaded devices.…”
Section: Transdermal Insulin Administrationmentioning
confidence: 99%